SOPHIE’S NEEDS IN ROOFTOPPERS NOVEL BY USING MASLOW’S THEORY OF HIERARCHY OF HUMAN NEEDS - Yunadi, Akbar; Kuncara, Singgih Daru; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
This research aimed to analyze Sophie’s needs based on the theory of Hierarchy of Human Needs by Abraham Harold Maslow. The purposes of this research were to find out the needs of the main character from the Rooftoppers novel and also finding how she fulfills all her needs. This research used descriptive qualitative research because the data were shown in words. There were two discussions taken in this research. First, is the identification of Maslow’s hierarchy of needs in the novel through the main character. The second is the identification of how the main character fulfill her needs according to Maslow’s theory. Rooftoppers novel was used in this research as the data source. The data consisted of paragraphs, phrases, words, and dialogues through the novel that showed Sophie’s needs. The results of the research showed that Sophie managed to fulfill all of her needs both at home and on her way of finding her long lost mother in Paris. Starting from the basic needs of physiological needs, safety needs, love and belonging needs, esteem needs, and self-actualization need. Sophie managed to fulfill all of her needs through her actions, dialogs, habits, and thoughts.